Deficiência mental: uma possibilidade de compreensão dos saberes de professores do ensino regular - Santos, Cleusa Aparecida de Oliveira (2007)
The present work aims to identify and understand the different acquirements found in the pedagogic practice of educators who work with bearers of deficiencies in the first-grade of elementary school. In order to achieve this objective, two public schools, which work under the perspective of inclusive education, located in the city of Uberlândia were chosen as a scenario. The study has started with a brief historic of Special Education and the definition and characteristics of mental deficiency. Afterwards, the educators knowledge and background were emphasized, favoring the understanding but the way these educators acquire and/or build and the mobilization of this knowledge, and what type of relation are established amongst themselves and their pedagogic practice. Through the nature of this work and the theoretical principles in which it is based, our methodological option was guided in a qualitative approach and it included the involvement of 3 specific educators who have students with mental deficiency in the first-grade, within your classrooms. In order to gather the data, it was used semi-structured interviews. The gathered information indicates that educators own a set of knowledge arising from all sort of sources and all of them are relevant for your professional performance, but the ones that most affect the pedagogic practice with the mental deficiency students in regular education, are the personal and experienced knowledge, whereas the educators do not have formation to work with these students. It was verified within this study that, in the lack of this formal initial knowledge, educators develop the work with the mental deficiency students searching inside their personal experiences and their auto-formation, and therefore, building their own set of experienced knowledge. In this way, the development of this work reveals the built knowledge of these three educators, in their performance with the mental deficiency student and it may contribute for the seek of alternatives to the initial and continuous formation, recognizing and valorizing the experienced knowledge built through the work development of the student. Add to that, It may also contribute to the reflection about the qualification of the educators.